Evaluating the Impact of Caffeine on the Incidence of Adverse Events During Treatment with Viloxazine Extended-Release (Qelbree®) in Adults with ADHD. (April 2023) - Nasser, Azmi; Gomeni, Roberto; Hull, Joseph; Maldonado-Cruz, Zulane; Earnest, Jami; Rubin, Jonathan
Abstract: Introduction: Viloxazine ER (viloxazine extended-release capsules (Qelbree ® ) is a novel, nonstimulant, FDA-approved treatment for attention-deficit/hyperactivity disorder (ADHD) in adults and children ≥6 years of age. Viloxazine ER inhibits cytochrome P450-1A2, the enzyme responsible for caffeine metabolism. In a Phase 1 study, the peak exposure (Cmax ) of caffeine was unchanged, while the systemic total exposure (AUC) was shown to increase ~5-fold following coadministration of caffeine (200mg) with viloxazine ER (900 mg/day x 4 days) compared to caffeine alone. Except for insomnia (44.4%), and possibly dizziness (8.3%), the incidence of adverse events (AEs) was not notably higher following coadministration vs. either caffeine or viloxazine ER alone. The objective of this analysis was to evaluate the impact of caffeine consumption on the incidence of AEs in adults with ADHD treated with viloxazine ER. Methods: Data were analyzed from the Phase 3, double-blind (DB), placebo-controlled trial (NCT04016779) and ensuing (ongoing) open-label extension (OLE) safety trial (NCT04143217) supporting the viloxazine ER indication for adults with ADHD. Participants reported caffeine intake during the past week at each study visit. Correlation was assessed between viloxazine ER dose (mg/day) and weekly total caffeine consumption (mg) and between ADHD Investigator Symptom Rating Scale (AISRS) Total score and caffeine consumption. Fifteen AE preferred terms, known to be associated with caffeine consumption, were evaluated. For viloxazine ER-treated subjects (200–600 mg/day) who experienced a potentially caffeine-associated AE, the probability the AE occurred as a function of viloxazine ER dose and caffeine consumption during the DB or OLE trials was estimated using a logistic regression model for AEs with an incidence ≥5%. Results: Of 372 enrolled subjects ~85% reported caffeine use during the DB trial; mean caffeine use was 1034 mg/week for the placebo group and 859 mg/week for the viloxazine ER group. There was no correlation between viloxazine ER dose and caffeine consumption (p=0.73), nor between AISRS total score and caffeine consumption (p=0.908). Of subjects reporting caffeine use, 44 (DB placebo), 79 (DB viloxazine ER), and 33 (OLE viloxazine ER) reported any of the pre-identified caffeine- associated AEs and were included in the regression analysis. For these subjects, insomnia-related AEs, fatigue, nausea, headache-related AEs, decreased appetite, and somnolence-related AEs occurred in ≥5% of viloxazine ER-treated subjects. Based on the regression analysis, caffeine consumption significantly increased the probability of experiencing insomnia-related AEs only (p=0.02). Conclusions: This analysis suggests using caffeine concomitantly with viloxazine ER does not increase the likelihood of experiencing caffeine-related AEs except for insomnia. Still patients should be aware of the potential for viloxazine ER to augment caffeine exposure. Funding: Supernus Pharmaceuticals, Inc.